Methods of Conveying Information to Jurors: An Evidence Review - Chalmers, James (2018)
Paper suggests that jurors can face considerable challenges in recalling both the evidence and the legal directions in a criminal trial and that they can struggle to understand legal directions. Eight possible methods of improving juror memory and/or understanding were identified: trial transcripts, juror note-taking, audio-visual and digital presentation methods, juror questions, pre-instruction, plain language directions, written directions and structured decision aids (routes to verdict)